Effects of different nitric oxide synthases on pulmonary and systemic hemodynamics in hypoxic stress rat model - Huan Zhang; Yu Zhang; Xiaojun Wang; Jie Liu; Wei Zhang (Animal Models and Experimental Medicine)
Abstract Background Under hypoxia, exaggerated compensatory responses may lead to acute mountain sickness. The excessive vasodilatory effect of nitric oxide (NO) can lower the hypoxic pulmonary vasoconstriction (HPV) and peripheral blood pressure. While NO is catalyzed by various nitric oxide synthase (NOS) isoforms, the regulatory roles of these types in the hemodynamics of pulmonary and systemic circulation in living hypoxic animals remain unclear. Therefore, this study aims to investigate the regulatory effects of different NOS isoforms on pulmonary and systemic circulation in hypoxic rats by employing selective NOS inhibitors and continuously monitoring hemodynamic parameters of both pulmonary and systemic circulation. Methods Forty healthy male Sprague–Dawley (SD) rats were randomly divided into four groups: Control group (NG‐nitro‐D‐arginine methyl ester, D‐NAME), L‐NAME group (non‐selective NOS inhibitor, NG‐nitro‐L‐arginine methyl ester), AG group (inducible NOS inhibitor group, aminoguanidine), and 7‐NI group (neurological NOS inhibitor, 7‐nitroindazole). Hemodynamic parameters of rats were monitored for 10 min after inhibitor administration and 5 min after induction of hypoxia [15% O2, 2200 m a. sl., 582 mmHg (76.5 kPa), Xining, China] using the real‐time dynamic monitoring model for pulmonary and systemic circulation hemodynamics in vivo. Serum NO concentrations and blood gas analysis were measured. Results Under normoxia, mean arterial pressure and total peripheral vascular resistance were increased, and ascending aortic blood flow and serum NO concentration were decreased in the L‐NAME and AG groups. During hypoxia, pulmonary arterial pressure and pulmonary vascular resistance were significantly increased in the L‐NAME and AG groups. Conclusions This compensatory mechanism activated by inducible NOS and endothelial NOS effectively counteracts the pulmonary hemodynamic changes induced by hypoxic stress. It plays a crucial role in alleviating hypoxia‐induced pulmonary arterial hypertension.